Inspiration from the development of public administration in the West for studies of public administration in China - Dong, Lisheng (Array, 2019)
Many Western-based theories of public administration have had some traction in the Chinese setting. However, they also point to the importance of context and the need to ensure that the theory is relevant to the setting. In this regard, theory needs to be both clearly developed and there are various routes that can be taken. In this article, I share with readers some of my thoughts emanating from my teaching and research over the past two decades, namely, inspiration from the development of public administration in the West for studies of public administration in China. The two analytical lenses that I use for this article are the five essential attributes of public administration and the instrumental and value rationalities as the fundamental nature of the various schools of thought in the development of public administration in the West. The five essential attributes refer to core value, assumptions about human nature, methodology, government role, and disciplinary positioning. They serve as references for my review of the field of public administration in China. Over the last four decades, public administration research in China has resulted in the restoration of the discipline, the flourishing of teaching and research programmes, and active exchanges with colleagues around the world. However, Chinese public administration is facing an “identity crisis”. Chinese scholars have become used to playing the role of consumers of imported concepts, theories, and methods. At this stage it is urgent that they develop their own unique paradigm, including concepts, theories, and methodologies, and contribute to the progress of the whole discipline. The goal of forming their own theoretical framework is urging our Chinese colleagues to challenge themselves to consciously engage in independent theoretical thought.